Investigation on the Origin of Al2O3‐Rich Inclusions in Valve Spring Steel under Vacuum Condition. Issue 7 (15th December 2016) - Chen, Liangjun; Chen, Weiqing; Hu, Yang; Chen, Zhaoping; Xu, Yingtie; Yan, Wei
Abstract : Hard and non‐deformable Al2 O3 ‐rich (>70 mass%) inclusions are extremely detrimental for valve spring wire. In order to explore the origin of Al2 O3 ‐rich inclusions and provide solutions, an investigation on the effects of Al‐containing MgO–C refractory and refining slag on the generation of Al2 O3 ‐rich inclusions in valve spring steel deoxidized by Si and Mn under different vacuum conditions is carried out on a laboratorial scale by a cold crucible levitation melting (CCLM) furnace. The experimental results indicate that the refractory/steel interaction under vacuum conditions has a far more significant contribution to the increase of [Al]S (Acid‐soluble Al) content in steel compared with slag/steel interaction, which further leads to the generation of Al2 O3 ‐rich inclusions. Based on the experimental results and thermodynamic calculations, the mechanisms of refractory/steel interaction and slag/steel interaction under vacuum conditions are deduced to provide a reference for the control of Al2 O3 ‐rich inclusions in valve spring steel deoxidized by Si and Mn. Abstract : A study on the source of Al2 O3 ‐rich inclusions in valve spring steel is conducted through vacuum cold crucible levitation melting method . The results demonstrate dissolution of Al antioxidant in MgO–C refractory instead of reduction of Al2O3 in slag during VD process should be primarily responsible for the formation of Al2O3‐rich inclusions. Finally, a potential control method is also proposed.